1994
DOI: 10.1590/s0102-311x1994000300017
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de Vibrio parahaemolyticus em mexilhões (Perna perna, Linnaeus, 1758) de banco natural do litoral do município de Palhoça, Santa Catarina, Brasil

Abstract: A study was carried out on the occurrence of Vibrio parahaemolyticus in forty samples of mussels (Perna perna, Linnaeus, 1758) from a natural bed at Pinheira Beach, Municipality of Palhoça, Santa Catarina (Brazil), during a three-month period. The most probable number technique was used for isolation methodology with prior enrichment of samples in alkaline peptone water and subsequent planting on thiosulfate citrate bile salts sucrose agar. Vibrio parahaemolyticus was found in 52.5% of samples of mussels with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
2
0
3
Order By: Relevance
“…In the present study it was observed that one strain showed beta-hemolysis on Wagatsuma agar (Kanagawa positive) but it was negative for tdh gene. This phenomenon has been reported in Brazil 1,4,16,24,32 and might be due to deletion or mutation in the tdh gene 33 .…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In the present study it was observed that one strain showed beta-hemolysis on Wagatsuma agar (Kanagawa positive) but it was negative for tdh gene. This phenomenon has been reported in Brazil 1,4,16,24,32 and might be due to deletion or mutation in the tdh gene 33 .…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, V. parahaemolyticus infections have increased globally 28,33 . Studies in Brazil demonstrated the presence of V. parahaemolyticus in environmental samples from a variety of sources as well as in clinical samples 1,25,26,27,31,34,35,38 . In 2002, according to data of the National Health Foundation (FUNASA), in Ceará, Brazil, an outbreak of gastroenteritis occurred, and Kanagawa-positive strains of V. parahaemolyticus serovar O3:K6 were isolated 31 .…”
Section: Introductionmentioning
confidence: 99%
“…No presente trabalho, o isolamento do micro-organismo realmente ocorreu em um mês no qual a salinidade estava dentro deste intervalo, em 4%. Em estudo desenvolvido por Archer & Moretto (1994), foi analisada a presença de V. parahaemolyticus em mexilhões, aferindo temperatura e salinidade nos dias de coleta. Os autores isolaram o micro-organismo de 52,5% (21/40) das amostras obtidas de ambiente com 35,6‰ de sanilidade e temperatura de 25,4°C.…”
Section: Resultsunclassified
“…Estes valores mais elevados possivelmente favoreceram a ocorrência de V. parahaemolyticus, permitindo um maior número de isolamentos quando comparado ao nosso trabalho. Segundo ICMSF (1978), V. parahaemolyticus é encontrado com maior frequência em estuários, sedimentos, moluscos e crustáceos, portanto as espécies das quais Archer & Moretto (1994) obtiveram os isolamentos também pode ser um fator para as diferenças observadas.…”
Section: Resultsunclassified
“…Além das implicações ambientais desta falta de controle, existe o risco à saúde humana, sendo que os testes e índices qualidade de água para a retirada de marisco e de análise microbiológica para garantir a qualidade dos mariscos foram estabelecidos pelas Portarias n° 204, de 28 junho de 2012 e n° 175, de maio de 2013, do Ministério da Pesca e Agricultura (MPA). Os riscos apresentados pelo marisco são vários, como toxina ácido ocadáico (Lourenço et al, 2007), metais pesados, como o cromo (Campolim et al, 2018), e a bactéria Vibrio parahemolyticus, já detectada em mexilhões coletados na grande Florianópolis (Archer & Moretto 1994;Helen et al, 2016).…”
Section: Normas Aplicáveisunclassified